A new approach to the content of environmental law - Cárdenas Velarde, Roy (2021)
In this article, the author addresses different problems that require urgent attention from countries, companies and civil society, based on the different columns written for the Official Newspaper El Peruano. In most cases it is stated that the problems are “environmental”; however, the author shows us how these are, before being environmental, society’s problems. The fight against climate change is the fight against an invisible friend, who each time connects us with an endless number of jabs, and the time will come when it will only be up to thereferee to do the counting.